2020
DOI: 10.1002/pd.5833
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution epigenomic liquid biopsy for noninvasive phenotyping in pregnancy

Abstract: Objective We explored the potential of genome‐wide epigenomic liquid biopsy for the comprehensive analysis of cell‐free DNA (cfDNA) methylation signatures in maternal plasma in early gestation. Method We used solution phase hybridization for targeted region capture of bisulfite‐converted DNA obtained from plasma of pregnant women in early gestation and nonpregnant female controls. Results Targeted sequencing of ~80.5 Mb of the plasma methylome generated an average read depth across all 17 plasma samples of ~42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The potential applications of this study to human health and patient diagnostics are substantial. Past research has shown liquid biopsy as a possible diagnostic technique for PE [ 50 , 51 , 52 ]. These assays rely on cell-free nucleic acids in blood plasma to identify differentially methylated regions indicative of disease states.…”
Section: Discussionmentioning
confidence: 99%
“…The potential applications of this study to human health and patient diagnostics are substantial. Past research has shown liquid biopsy as a possible diagnostic technique for PE [ 50 , 51 , 52 ]. These assays rely on cell-free nucleic acids in blood plasma to identify differentially methylated regions indicative of disease states.…”
Section: Discussionmentioning
confidence: 99%